An agile radio for wireless innovation. - Minden, Gary J.
We present the details of a portable, powerful, and flexible software-defined radio development platform called the Kansas University Agile Radio (KUAR). The primary purpose of the KUAR is to enable advanced research in the areas of wireless radio networks, dynamic spectrum access, and cognitive radios. We describe the KUAR hardware implementation and software architecture and present example application of the KUAR to modulation, spectrum measurement, channel estimation, and rapid configuration and adaptation. We outline research directions enabled by the KUAR.
Keywords: Kansas University Agile Radio; Agile radio; Channel estimation; Cognitive radios; Dynamic spectrum access; Modulation; Software architecture; Software-defined radio development platform; Spectrum measurement; Wireless radio networks